Stability evaluation and mitigation strategies in advanced tokamaks using 3D MHD spectroscopy - S.M. Yang; S. Munaretto; T. Liu; Q. Hu; C. Holcomb; N.C. Logan; B. Victor; K. Erickson; A. Bortolon (Nuclear Fusion)
Multi-modal, active 3D MHD spectroscopy is applied in high-performance advanced tokamak scenarios to study their stability time evolution, revealing an intriguing dependence on both $q_min$ and $β_\mathrm N$ . A tailored applied 3D field provides a 3D plasma response to extract the growth rate of the least stable mode. The estimated growth rate finds a decrease in stability when the minimum in the safety factor ( q ) passes through 2.0 and reveals inherent risks of crossing an additional rational surface at integer $q_min$ , even above the usual q = 1 sawtooth condition. Based on this result, the potential scenario in which $q_min \sim 2$ can be safely crossed during a more stable lower $β_\mathrm N$ phase was investigated, and the improved stability of this scenario is confirmed by the estimated growth rate. This shows that 3D MHD spectroscopy can offer insights into strategies for improving stability by identifying the vulnerable aspects of such scenarios. In addition, the method highlights its potential for instability avoidance by enabling early detection of multiple modes, even before magnetic coils can measure them. The measured growth rate by the 3D MHD spectroscopy shows its reliability by exhibiting a correlation with the programmed rises in plasma beta across various high $β_\mathrm N$ and high $q_min$ discharges. In addition, this method is successfully applied during rapidly evolving $I_\mathrm p$ ramp-up phases, a key part of the scenario development. By achieving reasonable growth rate measurements at high-performance scenario developments, this technique contributes to the development of advanced diagnostic tools for tokamak scenario stability, which will help identify an effective pathway to stable, high-performance scenarios.